ANTARA TRADISI DAN MODERNITAS: ANALISIS PERBANDINGAN PENDIDIKAN KARAKTER INDONESIA, INGGRIS, JEPANG DAN MALAYSIA - Zilfa, Rohil (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2023)
This study aims to explore the implementation of character education in four countries: Indonesia, Japan, Malaysia, and the United Kingdom. Each country has a different approach to shaping students' character, influenced by cultural factors, policies, and education systems. The study used a descriptive qualitative method to explore the literature and policies on character education in each country. The results showed that in Japan, character education is centered on the family with the philosophy of "ryosai kentro", while in Malaysia character education is inserted into the hidden curriculum through Islamic Religious studies. In Indonesia, character education is based on the values of Pancasila and government policies. The United Kingdom, influenced by the thinking of Thomas Lickona, focuses character education on morals to support democracy. Each country has succeeded in implementing character education in different ways but culminating in the formation of dignified human beings